Scheduling Of The Crystal Sugar Production System in Sugar Factory Using Max-Plus Algebra - Desi Indriyani; Subiono Subiono (LPPM Institut Teknologi Sepuluh Nopember, 2016)
Sugar is the main trading commodity besides as basic human needs and be a source of energy and mostly traded in the form of solid crystals of sucrose or crystal sugar with cane as raw materials. Sugar production process is very complicated because it had to pass through various stages that require considerable time. The number of machines used in production system affects the complexity in the calculation of production scheduling. In addition, if there are errors in analyzing the operating time that is different for each product, it will cause a chaos in the production scheduling. These conditions encourage us to conduct a study on the production flow or flow lines with buffer. The buffer is used on multiple processors as a placeholder for semi-finished material before it is processed in the next processors. Buffers are used in the form of vessels with varying volume. In this study, the max-plus algebra is the method used to obtain crystal sugar production scheduling system in the sugar factory. From the flow lines that have been made then we derive a model of max-plus algebra to obtain a production schedule that starts with the milling process to obtain crystal sugar. Based on the max-plus algebra model, we also obtained sugar output schedule and some kind of waste. In addition, we obtained two periodicities of each processor, that is from milling processor until sulfitation of thick juice processor with periodicity 177.64 minutes and from vacuum pan A processor until mixer D2 processor with periodicity 1592.63 minutes, from these periodicities, we obtain a periodic production schedule for each processor.